Gambaran Karakteristik Penderita Diabetes Mellitus Pada Beberapa Puskesmas di Kabupaten Gorontalo - Zul Adhayani Arda; Abd. Rahmat Ngobuto (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2019)
Diabetes Mellitus is a chronic metabolic disorder caused by inadequate insulin produced of the pancreas, or a state of the body that cannot use insulin effectively. During the last decade the prevalence of diabetes in low and middle income countries has increased. In 2018, Gorontalo Province ranks eighth for the highest prevalence of Diabetes Mellitus in Indonesia. The purpose of this study aims to description of the characteristics patient with Diabetes Mellitus in several Health Center in Gorontalo District. The study was an observational with descriptive design. The sample in this study was 313 people with diabetes mellitus who were selected as samples in Gorontalo District, who were selected by stratified random sampling technique. Univariate data analysis. The results of this study indicate that there are five health center studied, namely Limboto, Dungaliyo, Tabongo, Batudaa, and Pulubala Health Center. From the 313 respondents suffering from Diabetes Mellitus, 224 people (71.6%) were female, 230 people (73.5%) in the adult category, 271 people (86.6%) were married, 202 people (64.5) %) not working, 94 people (30%) have education levels only up to elementary school level, and 265 people (84.7%) with new status suffer from diabetes mellitus (<10 years). By looking at patient characteristics from the results of the study, it is expected that the health center as a health service provider can improve the Diabetes Mellitus prevention program, especially for preventive and promotive programs.